2007
DOI: 10.4161/cc.6.17.4644
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Hedgehog in T-Cell Receptor Signaling: Implications for Development and Immunity

Abstract: The Hedgehog (Hh) signaling pathway is a key regulator of both embryonic development and homeostasis of adult tissues, including thymus and blood. In the thymus, Hh signals for differentiation, survival and proliferation in the early stages of T cell development, before TCR gene rearrangement. Our recent data has shown that Hh signaling also modulates T cell receptor (TCR) signal strength in more mature T lineage cells. We showed that constitutive activation of the Hh pathway in thymocytes (by transgenic expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 65 publications
2
27
1
Order By: Relevance
“…As our findings were in contrast to several other reports describing an influence of Hh signaling on the transition from the double-positive (DP) to the single-positive (SP) stage of thymocyte development [22], [23], [24], we decided to repeat the analyses with mice backcrossed to the C57BL/6 background. Although the overall thymic cellularity (Figure 1A) and the percentages of double-negative (DN) thymocytes (Figure 1B,C) were similar in both genotypes, we found that the relative number of DP thymocytes was increased in Ptch flox/flox CD4Cre +/− mutant mice while the percentages of CD4 and CD8 SP thymocytes were decreased (Figure 1C).…”
Section: Resultscontrasting
confidence: 74%
“…As our findings were in contrast to several other reports describing an influence of Hh signaling on the transition from the double-positive (DP) to the single-positive (SP) stage of thymocyte development [22], [23], [24], we decided to repeat the analyses with mice backcrossed to the C57BL/6 background. Although the overall thymic cellularity (Figure 1A) and the percentages of double-negative (DN) thymocytes (Figure 1B,C) were similar in both genotypes, we found that the relative number of DP thymocytes was increased in Ptch flox/flox CD4Cre +/− mutant mice while the percentages of CD4 and CD8 SP thymocytes were decreased (Figure 1C).…”
Section: Resultscontrasting
confidence: 74%
“…30 Studies of the MAPK cascades activated during positive and negative selection have indicated that positively selected ligands induce a slow and sustained accumulation of Erk activity; in contrast, ligands that induce negative selection provoke a strong and transient burst of Erk phosphorylation. [31][32][33][34] Here we show that stimulation of AnxA1 -/-thymocytes with anti-CD3 caused a delayed and weaker phosphorylation of Erk1/2 compared to their NFκB than CD4 SP cells; and, furthermore, activation of this transcription factor determines the threshold of signalling responsible for positive and negative selection of MHC class I-restricted CD8 cells. [38][39][40] Our analysis of female HY-TCR/AnxA1 -/-thymocytes shows a significant impairment in the development of CD8 SP cells suggesting that reduced activation of NFκB in these cells might, at least, contribute to this phenotype.…”
mentioning
confidence: 61%
“…T-cell activation requires both T-cell receptor (TCR) and costimulatory molecule ligation by professional antigen-presenting cells (APC), and the outcome of the stimulatory signal is influenced by the microenvironment of the T cell and the APC. The Hh signaling pathway reduced the strength of the TCR signal in mature peripheral T cells (18,19). In addition, the repression of the Hh signaling pathway in T cells increased T-cell activation (20).…”
Section: Discussionmentioning
confidence: 99%